Increasing the Role of Educators as Student Learning Mentors in the Era of Society 5.0 - Nadia Marnia Titin; Achmad Supriyanto (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to explore the augmentation of teachers’ roles as learning mentors in the context of education in the Society 5.0 era. A descriptive qualitative approach was employed to obtain an in-depth understanding of how teachers’ roles develop in digital learning environments. The research was conducted at SD Lab UM Blitar, involving two teachers selected through purposive sampling. The research instrument consisted of semi-structured interview guidelines focusing on teachers’ role perceptions, mentoring practices, and forms of role augmentation. Data were collected through in- depth interviews, supported by field notes and audio recordings. Data analysis was carried out using an interactive model, including data reduction, data display, and conclusion drawing, while validity was ensured through source and method triangulation as well as member checking. The findings indicate that the teachers’ roles do not shift but expand through a process of functional enrichment. Teachers act as facilitators, learning guides, process directors, and character mentors. This study concludes that role augmentation is a gradual, contextual, and adaptive process that enhances the complexity of teachers’ professional roles without replacing their instructional functions.